Significant Correlation Between Pain Severity and Lumbosacral Radiology Findings in Patients with Low Back Pain - Shafira, Nabila Sarah; Laily Irfana; Muslim Andala Putra; Wirashada, Brilliant Citra (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Low Back Pain (LBP) is one of the most common pain complaints in daily life, with significant impacts on patients' quality of life. This study aims to analyze the correlation between pain severity, as measured by the Numeric Rating Scale (NRS), and lumbosacral radiographic findings in LBP patients at Siti Khodijah Sepanjang Hospital. This observational-analytical study used a cross-sectional design. A total of 45 patients who met the inclusion and exclusion criteria and had undergone a lumbosacral X-ray (AP/lateral) within the last 3 months were included in the sample. Pain severity was measured using the NRS questionnaire, and lumbosacral radiology findings were evaluated for muscle spasms, spondylolisthesis, osteophytes, intervertebral disc (IVD) narrowing, and compression fractures. The analysis revealed that 84.4% of patients experienced moderate pain. Regarding lumbosacral radiology abnormalities, 62.2% were classified as moderate in severity. Osteophyte formation was the most prevalent radiology finding, present in 86.7% of cases. Spearman's correlation test showed a significant correlation between pain severity and lumbosacral radiology findings (p = 0.00 < 0.05). The analysis demonstrated a strong, statistically significant positive correlation between radiology findings and pain severity (r = 0.62). These findings suggest that pain severity may serve as an indicator of the severity of lumbosacral radiological conditions in patients with low back pain and could be used as an adjunct in clinical evaluation and management strategies.